A comparison of cytokine responses during prolonged cycling in normal and hot environmental conditions - Ludmila M Cosio-Lima; Bhargav V Desai; Petra B Schuler; et al (Dove Medical Press, 2011)
Ludmila M Cosio-Lima, Bhargav V Desai, Petra B Schuler, Lesley Keck, Logan ScheelerDepartment of Health, Leisure, and Exercise Science, University of West Florida, Pensacola, FL, USAPurpose: Components of immune function are affected by physical activity in an adverse environment. The purpose of this study was to compare plasma differences in inflammatory cytokines including tumor necrosis factor α (TNF-α) and interleukin 6 (IL-6), in addition to the stress hormone cortisol, during prolonged cycling under normal and hot environmental conditions in elite cyclists.Methods and design: Six trained elite male cyclists (27 ± 8 years; 75.5 ± 4 kg; maximum oxygen uptake [VO2max] = 66 ± 6 mL/kg/min, mean ± SD). The cyclists biked for 2.5 h at their prescribed 60% maximum exercise workload (Wmax) or 75% VO2max either in an environmental chamber set at 15°C and 40% relative humidity (NEUTRAL) or at 35°C and 40% relative humidity (HOT). The cyclists were given 4 mL of water/kg body weight every 15 min under both conditions.Results: Total cortisol concentrations were elevated (P < 0.05) immediately postexercise and 12 h postexercise in both the NEUTRAL and HOT conditions. TNF-α concentrations were only significantly (P = 0.045) elevated postexercise in HOT conditions. During the HOT conditions, a significant (P = 0.006 and 0.007, respectively) difference in IL-6 was seen immediately after and 12 h postexercise. During the NEUTRAL condition, IL-6 was only significantly elevated postexercise (P < 0.05).Conclusions: Heat exposure during a long bout of exercise is sufficient to elicit stress response in elite cyclists. However, the degree of release of anti-inflammatory and proinflammatory cytokines might be related to several factors that include the athlete’s fitness level, hydration status, exercise intensity, and length of exposure to hot environments.Keywords: cytokines, inflammation, heat, exercise, performance